Formation of positive thinking as a factor of prevention of suicides in the student’s environment. (Journal of Educational Sciences, 2016)
In the article the authors propose to consider the process of formation of positive thinking as one of the links of preventive work on the prevention of suicides in the student’s environment. Recommendations for the organization of a positive attitude of students, there are several exercises curators-adviser on the formation of a warm and friendly relation in the student group, as well as in the opinion of the authors promote positive and optimistic perception of life.
Keywords: positive thinking; suicide; suicidal behavior; empathy understanding; optimistic attitude